A systematic and bibliometric review on millets as a sustainable solution to global hunger - Harini, S; Vennila , MA; Murugan, P P; Kavithamani , D; Padmarani , S; Sivakumar, C; Sangeetha, M (Plant Science Today, 2025)
Millets, often referred to as "climate-smart grains," play a vital role in global efforts to address hunger and malnutrition. This systematic review and bibliometric analysis examine the multifaceted contributions of millets to food security, nutrition enhancement and climate resilience. Globally, millet production reached approximately 30 million metric tons in 2023, with India contributing 41 % (12.2 million metric tons), followed by countries like Niger, China and Mali. Millets are nutrient-dense, containing 7-12 % protein, 2-5 % fat, 65-75 % carbohydrates and 15-20 % dietary fibre. The findings highlight their significance in resource-constrained and drought-prone regions, particularly in Asia and Africa, where millet-focused initiatives have shown promising outcomes. Despite these advantages, challenges such as limited policy support, low consumer acceptance and underdeveloped value chains persist, restricting their widespread adoption. This study identifies regional disparities in millet utilization and emphasizes the need for further research on processing technologies, market development and integration into mainstream dietary practices. By addressing these gaps, millets can play a transformative role in achieving global food security and advancing Sustainable Development Goal 2 (Zero Hunger), offering actionable insights for policymakers, researchers and stakeholders worldwide.